PERCEPTION OF DIFFERENT SMILE ARC TYPES IN ORTHODONTIC PATIENTS VISITING DENTAL SECTION AYUB MEDICAL COLLEGE - Niaz, Eizza; Ijaz, Wasim; Iqbal, Naveed; Naz Amir, Farida; Tariq, Afifa; Jadoon, Maidha; Saleem, Shizza (Journal of Ayub Medical College Abbottabad, 2024)
Background: The smile arc is one of the imperative components of an attractive smile. The objective of this study was to investigate the frequency of perception of orthodontic patients regarding various smile arc types and to assess awareness of their own smile arc. Methods: It was a single-center, cross-sectional study conducted at the Department of Orthodontics, Ayub Medical College, Abbottabad from December 2023 to January 2024. A sample of 126 participants was included through non-random consecutive sampling. Participants were asked to fill out a validated questionnaire to evaluate their perception regarding the smile arc. Results: In a study of 126 participants, majority were males and most belonged to age group 13–15 years. Among them 52.3% rated picture A as beautiful, while pictures B and C were rated as average by 58.7% and 40.5%, respectively. Age and occupation significantly influenced smile arc preferences (p<0.05). Overall, 62% correctly identified their smile arc, with no significant difference (p=0.80) between males (63%) and females (61%). Identification rates varied by age group and profession, though none were statistically significant (p=0.39 and p=0.13 respectively). Conclusion: The study revealed that the patients consistently rated consonant smile arcs as the most beautiful, while flat and reverse smile arcs were perceived as average. The study also highlighted the fact that patients visiting for orthodontic consultation are predominantly aware of their smile arc. These findings underscore the significance of dental harmony in shaping perceptions of facial attractiveness Keywords: Smile arc; Perception; Esthetics; Orthodontics